Synthesis of Axially Chiral Cationic Benzo[c]phenanthridinium Derivatives - Agudelo, Brian Castro; Rigoulet, Florian; Giorgi, Michel; Sayah, Babak; Rodriguez, Jean; Coquerel, Yoann (Synthesis, 2022)
Cationic polycyclic aromatic compounds containing one or more nitrogen atom(s), also known as azonia polycyclic aromatic compounds, form a valuable class of molecules because of their fluorescent and/or medicinal properties. N-Arylated hydroisoquinoline derivatives were synthesized through an aryne aza-Diels–Alder cycloaddition/N-arylation sequence. A subsequent two-electron oxidation allowed the synthesis of some axially chiral cationic benzo[c]phenanthridinium derivatives. The structural and optical properties of some of these molecules were determined. Their chirality was evidenced experimentally by single-crystal X-ray diffraction and 1H NMR spectroscopy, and their conformational behavior was examined by computational DFT methods.
Keywords: arynes; axial chirality; azadienes; azonia compounds; crystallography; DFT; fluorescence; rotamers